2020
DOI: 10.3389/fphar.2020.00102
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Stress Induces Depression-Like Behavior and Synaptic-Plasticity Changes in a Maternal Separation Rat Model: Gender Difference and Metabolomics Study

Abstract: More than 300 million people suffer from depressive disorders globally. People under early-life stress (ELS) are reportedly vulnerable to depression in their adulthood, and synaptic plasticity can be the molecular mechanism underlying such depression. Herein, we simulated ELS by using a maternal separation (MS) model and evaluated the behavior of Sprague-Dawley (SD) rats in adulthood through behavioral examination, including sucrose preference, forced swimming, and open-field tests. The behavior tests showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…In this study, we first confirmed that MS during infancy results in anxiety and depression-like behaviors in mouse, just as reported extensively [40,41]. In addition, we have shown that MS promotes the development of endometriosis and exacerbates endometriosis-associated generalized hyperalgesia in adult female mice, likely through decreased DRD2 expression and activation of the ADRB2/CREB signaling pathway, leading to increased angiogenesis and progression of endometriotic lesions.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we first confirmed that MS during infancy results in anxiety and depression-like behaviors in mouse, just as reported extensively [40,41]. In addition, we have shown that MS promotes the development of endometriosis and exacerbates endometriosis-associated generalized hyperalgesia in adult female mice, likely through decreased DRD2 expression and activation of the ADRB2/CREB signaling pathway, leading to increased angiogenesis and progression of endometriotic lesions.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to the anxiety phenotype, inconsistent behavior results for depressive-like behavior were reported for MS in rats ( 35 37 ). Our results showed that MSEW induced a passive coping strategy with increased immobility time in the forced swim test in male rats.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the dorsal hippocampus was also affected by MS, since the dentate gyrus showed significantly lower CCO in both male and female rats. ELS by MS during PND 14-21 [ 53 ] and PND 1-21 [ 54 ] has been reported to particularly affect the normal anatomical and functional development of the hippocampus and prefrontal cortex in rodents. In this regard, impaired spatial learning and memory in male rats and deficits in behavioral flexibility in female rats have been associated with hippocampal and prefrontal cortex dysfunction after MS in rodents [ 35 , 37 , 55 ].…”
Section: Discussionmentioning
confidence: 99%